STATUS STOK GENUS Rastrelliger spp. SEBAGAI DASAR PENGELOLAAN PERIKANAN (STUDI KASUS PERAIRAN SELAT SUNDA) - Wulandari Sarasati; Mennofatria Boer; Sulistiono Sulistiono (Jurnal Perikanan Universitas Gadjah Mada, 2016)
The Rastrelliger spp. is one of the important commodities of the Sunda Strait. This research aimsto analyze the stock status of Rastrelliger spp. Including R. faughni, R. kanagurta and R. brachysoma in Sunda Strait that landed at the Fishery Harbor (PPP) Labuan, Banten. The sampling was conducted in April-August 2015. The data was collected using Random stratified sampling based on the fish size, small, medium and large. The length of the sample was measured and classified into male and female. The data were analyzed using FISAT II ELEFAN I software to present the stock with growth, recruitment, surplus production model, and mortality and rate of exploitation parameters. The results show that R. faughni has L∞ values for females and males respectively of 264.00 mm and 288.69 mm, 293.09 mm and 330.24 mm R. kanagurta and R. brachysoma 272.04 mm and 286.42. Growth Performs Index (GPI) on R. faughni of 4.2758, R. kanagurta of 4.1673, and on R. brachysoma of 4.2076. The growth coefficient of female and male R. faughni was 0.22 and 0.16, R. kanagurta of 0.24 and 0.10, and R. brachysoma 0.20 and 0.13. The level of recruitment of each varies but overall undergoes two peaks during the recruitment period. Maximum Sustainable Yield (MSY) for the Rastrelliger spp. 1,919.02 tons and FMSY (Effort MSY) for 16,766 trips. Furthermore, the mortality rate of arrest (F) R. faughni amounted to 14.53, R. kanagurta 9.43, and R. brachysoma 1.74. The estimation of stock status has never been detached from the exploitation rate. The rate of exploitation for R. faughni, and that is equal to 0.98, R. kanagurta of 0.98, and R. brachysoma 0.85. Judging from the rate of exploitation can be expected the three fish of the Rastrelliger spp. In the Sunda Strait has been over exploited because it has exceeded the limits of optimum exploitation rate.